Del mass media, la comunicación y el desarrollo: anotaciones críticas sobre economía y medios (2010)
The technological revolution of the last twenty years has sparked new research concerns about the mass media, ones that have touched the general ideas of economic theory in relation to its development. This article takes an economic look at how the activity of the mass media has evolved. In doing so, it attempts to clarify the major stresses and strains of research in the field, in micro, meso and macroeconomic terms. It also discusses some of the regulatory implications in an effort to update the research agenda on the subject.